2016
DOI: 10.1002/cjas.1381
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of the UTAUT model: Eleven years later

Abstract: The unified theory of acceptance and use of technology (UTAUT) has been widely used to investigate factors influencing the adoption and use of information systems and technologies (IS/IT). However, studies using UTAUT are not conclusive in terms of statistical significance, direction, and magnitude. Through a meta-analysis of empirical studies on UTAUT from 2003 to 2013, we determine how parsimonious, accurate, and robust UTAUT is at predicting acceptance and use of technology. A meta-analysis of 74 publicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
133
4
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(173 citation statements)
references
References 37 publications
(74 reference statements)
30
133
4
6
Order By: Relevance
“…A metaanalysis of Khechine et al (2016) confirmed this result, asserting that even though the impact of behavioral intention on use behavior was classified as medium, the positive association between behavioral intention and use was confirmed. As previous literature concurs with Khechine et al (2016), supporting that intention is an antecedent of action, we propose to test the following hypothesis because we think that intention may often lead to a real use:…”
Section: Agementioning
confidence: 49%
See 1 more Smart Citation
“…A metaanalysis of Khechine et al (2016) confirmed this result, asserting that even though the impact of behavioral intention on use behavior was classified as medium, the positive association between behavioral intention and use was confirmed. As previous literature concurs with Khechine et al (2016), supporting that intention is an antecedent of action, we propose to test the following hypothesis because we think that intention may often lead to a real use:…”
Section: Agementioning
confidence: 49%
“…The UTAUT model is the result of a synthesis of eight theories of technology acceptance, diffusion, and use, usually employed in the management information systems field (theory of reasoned action of Fishbein and Ajzen (1975); technology acceptance model of Davis (1989); motivational model of Davis, Bagozzi, and Warshaw (1992); theory of planned behavior of Ajzen (1991); combined theory of planned behavior/technology acceptance model of Taylor and Todd (1995a); model of personal computer utilization of Thompson, Higgins, and Howell (1991); diffusion of innovation theory of Rogers (1995); and social cognitive theory of Compeau and Higgins (1995)). Venkatesh et al (2003) designed the UTAUT model to obtain a more exhaustive understanding and prediction of users' behavior that previous models could not achieve individually (Khechine, Ndjambou, & Lakhal, 2016). …”
Section: Elluminate As a Webinarmentioning
confidence: 99%
“…Secondly, UTAUT2 is a comprehensive core model that describes the key characteristics of intention to use WTDs, including the perception of the technology, hedonic motivation, and automatic outside‐task behaviour, such as habit. Finally, strong empirical support shows that UTAUT2 is one of the most comprehensive theories to use to understand consumer adoption (Khechine, Lakhal, & Ndjambou, ; Venkatesh et al, ).…”
Section: Theoretical Foundation and Research Modelmentioning
confidence: 99%
“…Effort expectancy is defined as the “degree of ease associated with the use of the system” (Venkatesh et al, , p. 450). Meta‐analysis studies of UTAUT have identified that the relationship between effort expectancy and intention to use has not been significant (Khechine et al, ; Sun et al, ). Other studies have shown that effort expectancy is no longer a barrier for the adoption of modern technology because consumers have enough experience and knowledge with the use of one technology to learn and use another (Gao et al, ; Wang, Jung, Kang, & Chung, ).…”
Section: Theoretical Foundation and Research Modelmentioning
confidence: 99%
“…Así, en los aproximadamente 15 años de vigencia ha sido aplicada de acuerdo a los requerimientos específicos de los investigadores (Lee, Korzan y Larsen, 2003;Venkatesh, Thong y Xu, 2016;Williams et al, 2011). En efecto, el interés ha sido impulsado por la constatación tanto teórica como empírica de que el éxito educativo de las herramientas tecnológicas depende del nivel de aceptación del usuario (Khechine, Lakhal y Ndjambou, 2016). Esta aceptación pasa necesariamente por lo que ellos creen que es útil, significativo y conveniente a su proceso de aprendizaje teniendo en cuenta la evolución de su pensamiento y madurez intelectual (Harteis, Gruber y Hertramph, 2010;Schommer, 1998).…”
Section: Discusión Y Conclusionesunclassified